If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + -1t = 3p Solving m + -1t = 3p Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add 't' to each side of the equation. m + -1t + t = 3p + t Combine like terms: -1t + t = 0 m + 0 = 3p + t m = 3p + t Simplifying m = 3p + t
| 0.4(x+50)+1.4x=101 | | 0.18(y-7)+0.12y=0.10y-1.5 | | 2f+11=4f-5 | | 18+u=-17 | | 6g-2=1+4g | | (2x+5)(x+1)=#8722;1 | | 6+6y=8y-10 | | 10x^2+9x-6=0 | | 5+2x=7-r | | 6x-5x+2=6+5x-4(1+4x) | | 4(a+3)=18-2(32-2a) | | log(I)=1.5 | | 100+2x=-500 | | 5w+21=8w-30 | | 100+2x=500 | | Y=4x^3-0.5x+2 | | 17.70=p+p(0.03)(6) | | F(x)=x^2-20 | | 0=4x^3-0.5x+2 | | 8v^2-8v-13=0 | | 0.80+x=252 | | F(x)=4x^3-0.5x+2 | | u-20=6u-120 | | 100-2x=500 | | (x-9)2=(x-3)2 | | 81=3w*9 | | s+2=3s-5 | | 9m+6n-2m+8n= | | 2m^2+6m-20=0 | | -14-x=-2x+10 | | 10x+6=10x-6 | | -x-85=-12x+179 |